1992
DOI: 10.1111/j.1399-6576.1992.tb03550.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated ventilatory response to hypoxaemia at vecuronium‐induced partial neuromuscular block

Abstract: The effect of a partial neuromuscular block on the ventilatory response to hypercarbia and to hypoxaemia was studied in 11 non-anaesthetized male subjects. Respiratory frequency, tidal volume, minute volume, respiratory timing and drive were measured during air breathing and during stimulation by hypercarbia and hypoxaemia. The ventilatory response was defined as the ratio between, respectively, tidal volume and minute volume during ventilation stimulated by hypercarbia and hypoxaemia compared to measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(57 citation statements)
references
References 18 publications
4
49
1
3
Order By: Relevance
“…[34][35][36] Further investigations specifically comparing recovery in the LA to that in the AP may be warranted. Data are presented as mean (SD).…”
Section: Méthodementioning
confidence: 99%
“…[34][35][36] Further investigations specifically comparing recovery in the LA to that in the AP may be warranted. Data are presented as mean (SD).…”
Section: Méthodementioning
confidence: 99%
“…Previous studies in volunteers have shown that pharyngeal function [2,3], airway muscle function [7], and also hypoxic ventilatory drive could be impaired [8,9], and residual paralysis could result in upper airway obstruction [7] and aspiration [3]. Clinical studies in surgical patients have also demonstrated a higher risk of critical postoperative respiratory events in patients with residual muscular blockade with a TOF ratio of \0.9 [10,11].…”
Section: Discussionmentioning
confidence: 95%
“…Currently used neuromuscular blockers are believed to be specific for muscle-type nAChRs. However, a series of studies in humans has shown that nondepolarizing neuromuscular blockers, such as vecuronium and pancuronium, inhibit hypoxic ventilatory responses at very low concentrations [116][117][118]. Igarashi et al hypothesized that vecuronium inhibits neuronal nAChRs in the carotid body, leading to depression of hypoxic ventilatory response [119].…”
Section: Vecuronium and The Carotid Bodymentioning
confidence: 98%